2000
DOI: 10.1128/mcb.20.18.6958-6969.2000
|View full text |Cite
|
Sign up to set email alerts
|

CDK9 Autophosphorylation Regulates High-Affinity Binding of the Human Immunodeficiency Virus Type 1 Tat–P-TEFb Complex to TAR RNA

Abstract: , and full-length CycT1 (amino acids 728) [CycT1(1-728)], but not truncated CycT1(1-303), was also phosphorylated by CDK9. P-TEFb complexes containing a catalytically inactive CDK9 mutant (D167N) bound TAR RNA weakly and independently of ATP, as did a C-terminal truncated CDK9 mutant that was catalytically active but unable to undergo autophosphorylation. Analysis of different Tat proteins revealed that the 101-amino-acid SF2 HIV-1 Tat was unable to bind TAR with CycT1(1-303) in the absence of phosphorylated C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
171
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(184 citation statements)
references
References 61 publications
12
171
0
1
Order By: Relevance
“…(ii) Two novel studies using the chromatin immunoprecipitation method have demonstrated that Ser-5, but not Ser-2, phosphorylation was dependent on transcription and that Ser-5-phosphorylated Pol II was primarily localized at promoter regions (23,54). In addition, two studies on human immunodeficiency virus type 1 gene transcription have reported that the transcriptional activator of this gene, Tat, stimulates both Ser-5 phosphorylation of the CTD of Pol II by Cdk9 and Pol II processivity for transcription elongation (12,73). These results all support the idea that Ser-5 phosphorylation makes Pol II processive in transcription.…”
Section: Discussionmentioning
confidence: 99%
“…(ii) Two novel studies using the chromatin immunoprecipitation method have demonstrated that Ser-5, but not Ser-2, phosphorylation was dependent on transcription and that Ser-5-phosphorylated Pol II was primarily localized at promoter regions (23,54). In addition, two studies on human immunodeficiency virus type 1 gene transcription have reported that the transcriptional activator of this gene, Tat, stimulates both Ser-5 phosphorylation of the CTD of Pol II by Cdk9 and Pol II processivity for transcription elongation (12,73). These results all support the idea that Ser-5 phosphorylation makes Pol II processive in transcription.…”
Section: Discussionmentioning
confidence: 99%
“…The unlabeled phosphoamino acid standards were visualized by staining the plate with ninhydrin; 32 P-labeled material was visualized by autoradiography. 32 P-Labeled phosphoamino acid analysis of autophosphorylated SpCdk9 and Pch1 was performed as follows. Reaction mixtures (200 l) containing 50 mM Tris acetate (pH 6.0), 1 mM DTT, 2.5 mM MnCl 2 , 50 M [␥-32 P]ATP, and 10 g of SpCdk9/Pch1 complex were incubated for 2 h at 22°C, then supplemented with 300 l of binding buffer B (50 mM NaH 2 PO 4 (pH 8.0), 50 mM NaCl, 7.5 mM imidazole, and 0.0025% Tween 20) and 50 l of nickel-agarose beads.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of the recombinant SpCdk9/Pch1 complex produced in baculovirus-infected insect cells showed that the S. pombe proteins comprise a bona fide protein kinase with a heterodimeric quaternary structure (30). The capacity of SpCdk9/Pch1 to phosphorylate the CTD arrays of both pol II and Spt5 in vitro echoed the substrate specificity of metazoan P-TEFb (11,12,31,32). These findings suggested a model whereby Spt5-induced arrest of early elongation ensures a temporal window for recruitment of the capping enzymes, which in turn attract Cdk9 to alleviate the arrest via phosphorylation of one or more components of the pol II elongation complex (30).…”
Section: Org/)mentioning
confidence: 99%
“…64 However, phosphorylation of CDK9 at this same residue, Thr186 and other residues is required for full enzymatic activity at promoters. [64][65][66][67][68][69] These studies suggest dynamic cycles of phosphorylation and dephosphorylation regulate P-TEFb activity to control the release of the RNA Pol II into productive elongation.…”
Section: Acknowledgmentsmentioning
confidence: 99%